2017
DOI: 10.1111/acel.12683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cell distribution and diabetes status on the association between mitochondrial DNA copy number and aging phenotypes in the InCHIANTI study

Abstract: SummaryMitochondrial DNA copy number (mtDNA‐CN) estimated in whole blood is a novel marker of mitochondrial mass and function that can be used in large population‐based studies. Analyses that attempt to relate mtDNA‐CN to specific aging phenotypes may be confounded by differences in the distribution of blood cell types across samples. Also, low or high mtDNA‐CN may have a different meaning given the presence of diseases associated with mitochondrial damage. We evaluated the impact of blood cell type distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
2
26
1
Order By: Relevance
“…Studies that use multiple mitochondrial biomarkers have revealed only a slight intercorrelation between the markers and aging, suggesting that they tap into different biological dimensions (Lara et al, 2015;Larsen et al, 2012;Marrocco, Altieri, & Peluso, 2017;Xia, Chen, McDermott, & Han, 2017). Recent data support the hypothesis that mtDNA copy number and degree of heteroplasmy-assessed in human blood cells and in tissue biopsies-provide information on mitochondrial physiology that is relevant for aging and age-related diseases (McDermott et al, 2018;Moore et al, 2017;Zhang, Wang, Ye, Picard, & Gu, 2017). Both measurements can be utilized via PCR methods or, more recently, by derivation from genome sequencing data (Ding et al, 2015).…”
Section: Mitochondrial Functionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies that use multiple mitochondrial biomarkers have revealed only a slight intercorrelation between the markers and aging, suggesting that they tap into different biological dimensions (Lara et al, 2015;Larsen et al, 2012;Marrocco, Altieri, & Peluso, 2017;Xia, Chen, McDermott, & Han, 2017). Recent data support the hypothesis that mtDNA copy number and degree of heteroplasmy-assessed in human blood cells and in tissue biopsies-provide information on mitochondrial physiology that is relevant for aging and age-related diseases (McDermott et al, 2018;Moore et al, 2017;Zhang, Wang, Ye, Picard, & Gu, 2017). Both measurements can be utilized via PCR methods or, more recently, by derivation from genome sequencing data (Ding et al, 2015).…”
Section: Mitochondrial Functionmentioning
confidence: 88%
“…Both measurements can be utilized via PCR methods or, more recently, by derivation from genome sequencing data (Ding et al, ). High mtDNA copy number is considered to be a proxy measure of mitochondrial volume/function, and high mtDNA copy number in blood is associated with better health and survival among older persons, but the direction of this association may be reversed in certain conditions, such as diabetes (Mengel‐From et al, ; Moore et al, ). Humans have detectable levels of mtDNA‐acquired point mutations in circulating cells and whole blood and, notably, the burden of mutations increase with aging even when measured in inducible pluripotent stem cells (Kang et al, ; Qian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To validate mtDNA-CN measurements in the filtered GTEx data, we determined the association between mtDNA-CN and known correlated measures, including age, sex, and neutrophil count [18,20,21]. We observed a significant association with neutrophil count (p=5e-05), with higher neutrophil count associated with lower mtDNA-CN.…”
Section: Determination and Validation Of Mtdna-cn Metricmentioning
confidence: 94%
“…Indeed, we Importantly, our results indicate that MT DNA abundance is negatively associated with increased age, higher frailty, increased smoking behaviour as well as increased BMI. We hypothesized that MT copy number may be diminished due to lower rates of replication with increasing age20,21 , due to oxidative stress induced by smoking22 , by low-grade inflammation and metabolic stress due higher BMI20 or due to prior health related conditions (as expressed by the frailty index)23,24 . Since individuals with a healthier lifestyle tend to have higher MT DNA abundance, we also observed a reduced incidence of hypertensive disorders such as portal hypertension and cardiomegaly as well as lower mortality in those individuals.…”
mentioning
confidence: 99%